Low-temperature-resistant high-impact ASA rubber powder as well as synthesis method and application thereof

By using butyl acrylate, styrene and methyl methacrylate as monomers, combined with semi-continuous seed emulsion polymerization technology and secondary core layer growth process, a high-performance core-shell structure copolymer was designed, solving the problems of poor impact resistance and high material cost of existing ASA powder under low temperature conditions, and achieving the effect of significantly improving the impact strength of low temperature notch and reducing material cost.

CN119638903APending Publication Date: 2025-03-18ZHEJIANG KEPUTE NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411911029.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing ASA glue powder has poor impact resistance under low temperature conditions, high material cost, and insufficient high temperature resistance and coloring ability.

Method used

Using butyl acrylate, styrene and methyl methacrylate as monomers, a core-shell structure copolymer with butyl acrylate as the core and styrene and methyl methacrylate as the shell was designed through semi-continuous seed emulsion polymerization technology, and its toughness and heat resistance were further enhanced through the secondary core layer growth process.

Benefits of technology

It significantly improves the impact strength of low-temperature notched under low temperature conditions, reaching ≥6.8 KJ/m2, and reduces material costs, improves heat resistance and coloring capabilities, and meets the requirements of high-quality automotive parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638903A_ABST
    Figure CN119638903A_ABST
Patent Text Reader

Abstract

The invention belongs to functional materials, and relates to synthesis of ASA, in particular to low-temperature-resistant and high-impact ASA rubber powder as well as a synthesis method and application thereof, and an alloy blended by the low-temperature-resistant and high-impact ASA rubber powder and SAN has remarkable low-temperature impact resistance. According to the invention, butyl acrylate, styrene and methyl methacrylate are mainly adopted as monomers, and a secondary core layer growth process is combined to endow a polymer with toughening performance, rigidity and dimensional stability, and excellent weather resistance, aging resistance, chemical resistance and yellowing resistance; the core-shell structure copolymer with butyl acrylate as a core and styrene and methyl methacrylate as a shell is designed in a semi-continuous seed emulsion polymerization mode, the glass transition temperature is lower, and furthermore, the material obtained after the SAN resin is modified by the core-shell structure copolymer has very good low-temperature notch impact strength, and can be applied to the field of emulsion polymerization. The blackness L value can reach 7 KJ / m < 2 >, meanwhile, the blackness L value effect is met, the highlight effect is achieved, and the requirements of high-quality automobile parts are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to functional materials and relates to the synthesis of ASA, in particular to a low-temperature-resistant and high-impact ASA rubber powder and a synthesis method and application thereof. The alloy blended with SAN has significant low-temperature impact resistance. Background Art

[0002] ASA rubber powder is composed of acrylic ester monomers as core monomers, which give the polymer impact resistance and aging resistance, acrylonitrile and styrene as shell monomers, which give the polymer excellent gloss, processability, excellent rigidity and chemical resistance. The three compounds are synthesized into a ternary copolymer with a core-shell structure through semi-continuous seed emulsion polymerization. The prior art discloses a method for preparing ASA resin, specifically a method for preparing an agglomerating agent with a specific structure, and a method for preparing a high-strength ASA resin by regulating the particle size of acrylic rubber through the agglomerating agent. The mechanical properties of the ASA resin prepared by this method are relatively low. The prior art first synthesizes butyl acrylate seed latex, then expands the diameter of butyl acrylate to obtain a rubber latex with a suitable particle size, and then uses styrene, acrylonitrile and methacrylate compounds for graft polymerization to obtain a copolymer latex, and finally obtains an ASA polymer through coagulation, centrifugation and drying. The prior art includes adding deionized water, a diameter expander, an emulsifier, an acrylate monomer, a crosslinking agent, and an initiator into a reaction vessel to obtain an acrylate seed latex; taking the acrylate seed latex, adding an acrylate monomer, and obtaining a core layer latex through reaction; adding styrene and acrylonitrile to the core layer latex, and grafting the monomers into the core layer latex to obtain a primary grafted polymer emulsion; mixing the remaining styrene and acrylonitrile, the emulsifier, and deionized water, and emulsifying to a stable emulsion; dropping the emulsion into the primary grafted polymer emulsion containing the initiator to react, and completing the secondary grafting polymerization through heating and aging, adding a composite antioxidant to the polymer emulsion, and obtaining an ASA resin high-rubber powder through condensation, dehydration, and drying; the diameter expander is one of trisodium phosphate, sodium chloride, potassium chloride, or sodium sulfate. The common problem of the existing prepared ASA polymers used in the toughening and modification of SAN plastics is that the low-temperature resistance and impact resistance modification effects are average. Summary of the invention

[0003] The present invention mainly adopts butyl acrylate, styrene and methyl methacrylate as monomers and combines the secondary core layer growth process to give the polymer toughening performance, rigidity and dimensional stability, excellent weather resistance, aging resistance, chemical resistance and yellowing resistance. A core-shell structure copolymer with butyl acrylate as the core and styrene and methyl methacrylate as the shell is designed by semi-continuous seed emulsion polymerization. The core-shell structure copolymer has a lower glass transition temperature. Furthermore, the core-shell structure copolymer of the present invention has very good low-temperature notched impact strength of the material modified by SAN resin, which can reach 7 KJ / m 2, while satisfying the effect of blackness L value, achieving a high gloss effect, meeting the requirements of high-quality automotive parts.

[0004] The present invention adopts the following technical solution: A method for synthesizing low-temperature-resistant and high-impact ASA rubber powder comprises the following steps: (1) adding part of the emulsifier solution, butyl acrylate, ethylene glycol dimethacrylate, and methyl silicone oil into a pre-emulsification bottle for pre-emulsification to obtain a core layer pre-emulsion; adding the remaining emulsifier solution, styrene, and methyl methacrylate into another pre-emulsification bottle for pre-emulsification to obtain a shell layer pre-emulsion; (2) Then, 1 to 10% of the core layer pre-emulsion and part of the initiator are added to a reaction vessel to carry out seed polymerization; then, the remaining core layer pre-emulsion is added dropwise to carry out core layer polymerization to obtain an acrylate latex; (3) 40-60% of the shell pre-emulsion and part of the initiator are added to the acrylic latex for a primary grafting reaction; then the remaining shell pre-emulsion and the remaining initiator are added for a secondary grafting reaction to obtain a low-temperature resistant and high-impact ASA rubber powder.

[0005] In the present invention, in step (1), the partial emulsifier solution is 40-60% of the total emulsifier solution, calculated by volume percentage.

[0006] In the present invention, in step (1), the pre-emulsification is carried out in water for 1 to 3 hours, preferably 1.5 to 2.5 hours.

[0007] In the present invention, in step (2), the seed polymerization is carried out in the presence of a pH buffer; the pH buffer includes an inorganic base.

[0008] In the present invention, in step (2), the partial initiator is 25-35% of the total initiator, calculated by weight percentage.

[0009] Preferably, in step (2), 2-8% of the core layer pre-emulsion is used; further preferably, in step (2), 3-7% of the core layer pre-emulsion is used, such as 4%, 5%, 6% or other values ​​within the range; calculated as volume percentage.

[0010] In the present invention, in step (2), the temperature of the seed polymerization is 60 to 70° C., and the time is 15 to 50 minutes, preferably 25 to 40 minutes.

[0011] In the present invention, in step (2), the remaining core layer pre-emulsion is added dropwise at 75-80°C.

[0012] In the present invention, in step (2), the temperature of the core layer polymerization is 75-80° C., and the time is 0.5-2 hours. Preferably, the temperature of the core layer polymerization is 75-77° C., and the time is 0.8-1.5 hours.

[0013] In the present invention, in step (3), 40-60% of the shell pre-emulsion is calculated by volume percentage; the partial initiator is 25-35% of the total initiator, calculated by weight percentage.

[0014] In the present invention, in step (3), the temperature of the primary grafting reaction is 75-80° C., and the time is 0.5-2 hours. Preferably, the temperature of the primary grafting reaction is 75-77° C., and the time is 0.8-1.5 hours.

[0015] In the present invention, in step (3), the temperature of the secondary grafting reaction is 75-80° C., and the time is 0.5-2 hours. Preferably, the temperature of the secondary grafting reaction is 75-77° C., and the time is 0.8-1.5 hours.

[0016] In the present invention, in step (3), the secondary grafting reaction is followed by conventional treatment to obtain low-temperature resistant and high-impact ASA rubber powder; the conventional treatment is an existing step for synthesizing ASA rubber powder, including emulsion coagulation, dehydration, and drying.

[0017] The invention discloses ASA rubber powder synthesized by the synthesis method of the low-temperature-resistant and high-impact-resistant ASA rubber powder.

[0018] The invention discloses a modified SAN resin, comprising the above-mentioned ASA rubber powder and SAN resin.

[0019] The invention discloses a preparation method of the modified SAN resin, comprising the following steps: melting and mixing raw materials containing the ASA rubber powder and the SAN resin to obtain the modified SAN resin.

[0020] Further, the raw materials comprising the above-mentioned ASA rubber powder and SAN resin are the above-mentioned ASA rubber powder and SAN resin; or the raw materials comprising the above-mentioned ASA rubber powder and SAN resin are the above-mentioned ASA rubber powder, SAN resin and other reagents.

[0021] In the above technical solution, other reagents include processing aids, colorants, etc., which can be selected by those skilled in the art according to production needs.

[0022] The invention discloses application of the ASA rubber powder in preparing modified SAN materials.

[0023] The invention discloses application of the ASA rubber powder in improving the low-temperature impact resistance of SAN materials.

[0024] The invention discloses application of the ASA rubber powder in preparing automobile SAN materials.

[0025] The invention discloses application of the ASA rubber powder in preparing automobile materials.

[0026] An automobile component, the raw materials for preparing the component include the above-mentioned ASA rubber powder or the above-mentioned modified SAN resin.

[0027] The invention uses deionized water to prepare emulsifier and initiator into solutions for standby use; the emulsifier solution, core layer monomers butyl acrylate and ethylene glycol dimethacrylate, and methyl silicone oil are added into a pre-emulsification bottle for pre-emulsification; then 4-6% of the core layer pre-emulsion and the initiator are added into a reaction container containing baking soda for seed polymerization; the core layer pre-emulsion is then added dropwise for core layer polymerization, and after the addition is completed, the reaction is performed to obtain acrylate latex; the emulsifier and shell layer monomers styrene and methyl methacrylate are pre-emulsified, and then half of the shell layer pre-emulsion is added dropwise to the reaction, and the initiator is added at the same time for primary grafting, after the reaction, the other half of the shell layer pre-emulsion and the initiator are added into the reaction for secondary grafting, and after the reaction, the temperature is naturally lowered to room temperature-50°C to obtain ASA emulsion; the emulsion is then condensed, dehydrated, and dried to obtain ASA resin high-rubber powder (MASA).

[0028] ASA resin high rubber powder is blended with SAN resin, and granulated by a twin-screw extruder to obtain modified SAN resin.

[0029] At present, domestic ASA rubber powder has the following defects: compared with some other thermoplastics with similar functions, ASA has high material cost, poor high temperature resistance, poor coloring ability, and poor impact resistance under low temperature conditions. The present invention reduces the material cost, and the synthesized ASA resin high rubber powder has good heat resistance (no discoloration at 150°C for 48 hours), a glass transition temperature of below -45°C, and good low temperature impact strength for SAN modification (low temperature notched impact strength ≥6.8 KJ / m 2 ). BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the infrared image of the emulsion in Example 1.

[0031] Figure 2 These are the heat resistance test results of different rubber powders. DETAILED DESCRIPTION

[0032] The common problem of the existing ASA polymer used in the toughening and modification of SAN plastics is that the low-temperature resistance and impact resistance modification effect is average. For example, the existing technology controls the mass content of polybutadiene in ABS resin to 12% to 18%, which can be coordinated with ASA rubber powder, SAN resin and anti-sounding additives to obtain an ASA / ABS composite material with good low-temperature toughness, and the notched impact strength at -30°C reaches 3-4kJ / m 2. Moreover, compared with some other thermoplastics with similar functions, ASA has high material cost, poor high temperature resistance, poor coloring ability, and poor impact resistance under low temperature conditions. The present invention reduces the material cost, and the synthesized ASA resin high rubber powder has good heat resistance (no discoloration at 150°C for 48 hours), a glass transition temperature of below -45°C, and good low temperature impact strength for SAN modification (low temperature notched impact strength ≥6.8 KJ / m 2 ).

[0033] The invention uses deionized water to prepare emulsifier and initiator into solutions for standby use; the emulsifier solution, core layer monomers butyl acrylate and ethylene glycol dimethacrylate, and methyl silicone oil are added into a pre-emulsification bottle for pre-emulsification; then 5% of the core layer pre-emulsion and the initiator are added into a reaction container, seed polymerization is carried out at 65°C, the reaction is carried out for 30 minutes, and the emulsion becomes transparent to blue light; the core layer pre-emulsion is then dripped at 76°C for core layer polymerization, and the reaction is carried out for 1 hour after the dripping is completed to obtain acrylate latex; the emulsifier and shell layer monomers styrene and methyl methacrylate are pre-emulsified, and then half of the shell layer pre-emulsion is dripped into the reaction, and the initiator is added at the same time for primary grafting, after the reaction is carried out for 1 hour, the other half of the shell layer pre-emulsion and the initiator are added into the reaction for secondary grafting, after the reaction is carried out for 1 hour, the temperature is naturally reduced to room temperature-50°C to obtain ASA emulsion; the emulsion is then condensed, dehydrated, and dried to obtain ASA resin high-glue powder.

[0034] In the present invention, the pre-emulsification is carried out in water for 1 to 3 hours, preferably 1.5 to 2.5 hours. Specifically, the monomer, emulsifier and deionized water are added to the reaction kettle in proportion, and stirred for two hours. The pre-emulsification is completed until the pre-emulsified liquid is not separated.

[0035] In the present invention, seed polymerization is carried out in the presence of a pH buffer; preferably, the pH buffer is an inorganic base, such as baking soda; further preferably, the amount of baking soda is 0.1 to 0.3% of the total mass of all monomers, such as 0.1%, 0.2%, 0.3% or any value within the range.

[0036] In the present invention, the initiator is selected from C3-C18 organic peroxides, such as one or more of diisopropylbenzene peroxide, isopropylbenzene hydroperoxide, and tert-butyl hydroperoxide; or the initiator is selected from persulfate; the persulfate preferably includes one or more of potassium persulfate and ammonium persulfate, preferably potassium persulfate.

[0037] In the present invention, the crosslinking agent is selected from one or more of aromatic compounds having vinyl groups and acrylate compounds, preferably one or more of divinylbenzene, ethylene glycol diacrylate, ethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, and 1,6-hexanediol dimethacrylate.

[0038] In the present invention, the emulsifier includes an anionic emulsifier and a nonionic surfactant. Preferably, the mass ratio of the anionic emulsifier to the nonionic surfactant is (2-6):1, such as 3:1, 4:1, 5:1; wherein the anionic surfactant is selected from one or more of alkyl sulfates, alkyl sulfonates, alkylbenzene sulfonates, and alkylnaphthalene sulfonates, including one or more of rosin soap, stearic acid soap, oleic acid soap, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate; the nonionic surfactant includes fatty alcohol polyoxyethylene ether (AEO).

[0039] In the synthesis method of the low temperature resistant and high impact resistant ASA rubber powder of the present invention, the monomer composition is as follows: Butyl acrylate balance Styrene 20-40% Methyl methacrylate 5-15% Methyl silicone oil 2-8% Preferably, in the synthesis method of the low temperature resistant and high impact resistant ASA rubber powder of the present invention, the monomer composition is as follows: Butyl acrylate balance Styrene 28-35% Methyl methacrylate 8-12% Methyl silicone oil 3-7% The mass sum of the monomers is 100%.

[0040] Furthermore, the mass percentage of butyl acrylate is 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60% or any proportion thereof; the mass percentage of styrene is 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35% or any proportion thereof; the mass percentage of methyl methacrylate is 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any proportion thereof; the mass percentage of methyl silicone oil is 4%, 5%, 6% or any proportion thereof.

[0041] In the synthesis method of the low temperature resistant and high impact resistant ASA rubber powder of the present invention, the weight of the monomers is 100%, and the auxiliary agent composition is as follows: Emulsifier (sodium lauryl sulfate, fatty alcohol polyoxyethylene ether) 0.5-1.5% Initiator (potassium persulfate) 0.3-1% Crosslinking agent (ethylene glycol dimethacrylate) 0.1-0.3% Preferably, in the synthesis method of the low temperature resistant and high impact resistant ASA rubber powder of the present invention, the weight of the monomers is 100%, and the auxiliary agent composition is as follows: Emulsifier (sodium lauryl sulfate, fatty alcohol polyoxyethylene ether) 0.8-1.2% Initiator (potassium persulfate) 0.5-0.8% Crosslinking agent (ethylene glycol dimethacrylate) 0.15-0.25% As an example, in the synthesis method of the low temperature resistant and high impact resistant ASA rubber powder of the present invention, the weight of the monomers is 100%, and the auxiliary agent composition is as follows: Emulsifier (sodium lauryl sulfate, fatty alcohol polyoxyethylene ether) 1% Initiator (potassium persulfate) 0.6% Crosslinking agent (ethylene glycol dimethacrylate) 0.2% As common sense, distilled water or deionized water is a dispersion medium, not a preparation raw material.

[0042] As common sense, after the secondary grafting reaction, conventional treatment is performed to obtain low-temperature resistant and high-impact ASA rubber powder; conventional treatment is the existing steps for synthesizing ASA rubber powder, including emulsion coagulation (flocculation), dehydration, and drying.

[0043] As an example, anhydrous magnesium sulfate solution is used for emulsion flocculation, preferably, the mass ratio of anhydrous magnesium sulfate to deionized water is 1:20. The emulsion is added dropwise to the flocculant solution (magnesium sulfate solution), the emulsion is diluted by one half, and flocculation is completed; then dehydration is carried out, and the solid matter is dried to obtain ASA rubber powder.

[0044] ASA resin high rubber powder is blended with SAN resin, and granulated by a twin-screw extruder to obtain modified SAN resin.

[0045] Preferably, during the blending modification, the raw materials comprising the above-mentioned ASA rubber powder and SAN resin are melt-mixed to obtain modified SAN resin. Further, the raw materials comprising the above-mentioned ASA rubber powder and SAN resin are the above-mentioned ASA rubber powder and SAN resin, and further preferably, the mass percentages of ASA rubber powder and SAN resin are as follows: ASA rubber powder 20-30% SAN resin 70-80% The following is an explanation of the technical progress of the present invention through specific experiments. The reagents used are existing products, and the specific preparation operations and performance tests are all conventional techniques.

[0046] Material description: Butyl acrylate (BA), styrene (St), acrylonitrile (AN), methyl methacrylate (MMA), methyl silicone oil, ethylene glycol dimethacrylate (EGDMA), fatty alcohol polyoxyethylene ether (AEO9) non-ionic emulsifier, sodium dodecyl sulfate (K12) anionic emulsifier, potassium persulfate (KPS), anhydrous magnesium sulfate demulsifier, and SAN resin (NX3400) are all commercially available products.

[0047] The formulas of the embodiments of the present invention and the comparative examples are shown in Table 1; the synthesis methods are as follows: (1) Use deionized water to prepare emulsifier (the proportion of K12 is 0.8% of the total monomer, the proportion of AEO9 is 0.2% of the total monomer, and the concentration of deionized water and emulsifier (total) is 5%) and initiator (the concentration of deionized water and initiator is 5%, and it is added evenly in batches during polymerization) into solutions for use; (2) Add the emulsifier solution (60% of the total emulsifier solution) and the core layer monomers butyl acrylate, ethylene glycol dimethacrylate, and methyl silicone oil (if any) into the pre-emulsification bottle for pre-emulsification to obtain a core layer pre-emulsion; (3) pre-emulsifying the emulsifier solution (40% of the total emulsifier solution, i.e., the remaining emulsifier) ​​with the shell monomers styrene and methyl methacrylate (or acrylonitrile) to obtain a shell pre-emulsified liquid; (4) Baking soda (0.2% of the weight of all monomers) and 5 times the weight of deionized water were added to a reaction container, and then 5% of the core layer pre-emulsion and the initiator solvent were added to the reaction container, and seed polymerization was carried out at 65°C for 30 minutes, and the emulsion became transparent to blue light; then, the core layer pre-emulsion was added dropwise at 76°C (dropwise for 2 hours) to carry out core layer polymerization, and the reaction was carried out for 1 hour to obtain an acrylate latex; (5) half of the shell pre-emulsion was added dropwise to the acrylic ester latex and the initiator solvent was added to perform a primary grafting (dropwise addition for 1 hour). After reacting at 76°C for 1 hour, the other half of the shell pre-emulsion and the initiator solvent were added to the reaction for a secondary grafting. After reacting at 76°C for 1 hour, the temperature was naturally lowered to 40°C to obtain the ASA emulsion. (6) The ASA emulsion is then condensed, dehydrated, and dried to obtain ASA resin high-rubber powder. This is a conventional method, which is briefly described as follows: anhydrous magnesium sulfate solution is used for emulsion flocculation, and the mass ratio of anhydrous magnesium sulfate to deionized water is 1:20; the emulsion is added dropwise to the flocculant solution (magnesium sulfate solution), the emulsion is diluted by half, and flocculation is completed; then dehydration is carried out and the solid matter is dried to obtain ASA rubber powder.

[0048] The polymerization atmosphere was a nitrogen atmosphere.

[0049] The performance results of the ASA rubber powder synthesized in the examples and comparative examples are shown in Table 1.

[0050] Extended Example ASA rubber powder was blended with SAN resin and granulated by a twin-screw extruder, which is a conventional technology. The test results are shown in Table 2.

[0051] The testing methods for materials are conventional techniques, which are briefly described as follows: Solid content of emulsion: prepare the test sample, take a clean and dry glass container, weigh it as m0, unit g; weigh 1g of emulsion (accurate to 0.1 mg), m1, unit g; put it evenly into a clean and dry glass container, and then dry it in a constant temperature blast drying oven at 105±2℃ for 3h to constant weight; take out the glass container and weigh it, m2, unit g; then the total solid content (TSC) of the emulsion is calculated as follows: TSC =

[0052] Monomer conversion rate: Monomer conversion rate is an important indicator to examine whether the emulsion polymerization emulsion reaction is complete. The monomer conversion rate is calculated as follows: Monomer conversion rate =

[0053] Where: G------total mass of emulsion, unit: g; TSC---Polymer emulsion solid content, unit: %; m4-----emulsifier mass, unit: g; m5-----Initiator mass, unit: g; m6-----emulsion gel mass, unit: g; m-----Total mass of polymerized monomers, unit: g.

[0054] Flocculation requirements: After magnesium sulfate flocculation and drying, the product yield reaches more than 95%.

[0055] Emulsion particle size: According to standard ASTM E79-03, weigh a certain amount of emulsion into a clean beaker, dilute it with deionized water to a mass fraction of 0.5‰, ultrasonicate for 20 min, let it stand for 2 h, take a portion and put it into a cuvette, use Malvern particle size analyzer to characterize the test sample, the particle size of the emulsion is required to be 250±10nm.

[0056] Notched impact strength: Low temperature condition is -30±2℃ for 4h, according to standard ISO 179-1eA, the test should be completed within 10s after low temperature treatment, the required value is ≥6.5KJ / m 2 .

[0057] Blackness: According to GB / T 7048-2012, the 10° / D65 SCI test method is adopted, and the reflectivity is used to express the blackness value of the sample, and the value is required to be ≥26.

[0058] Glass transition temperature: According to the standard GB / T 19466-2008, the sample is cut into uniform small pieces, usually 10 mg to 20 mg of sample is used, and the sample is loaded into the sample pan of the differential scanning calorimeter. The heating rate is 10℃ / min, and the test temperature range is between -120℃ and 300℃. The glass transition temperature is determined according to the DSC curve, and the required value is ≤-45℃.

[0059] Table 1 Examples and comparative examples formulation (Kg) and characterization

[0060] Contrast 6 Using the formula of Example 1, the synthesis method is as follows: (1) Use deionized water to prepare emulsifier (the proportion of K12 is 0.8% of the total monomer, the proportion of AEO9 is 0.2% of the total monomer, and the concentration of deionized water and emulsifier (total) is 5%) and initiator (the concentration of deionized water and initiator is 5%) into solutions for use; (2) Adding emulsifier solution (60% of the total emulsifier solution) and core layer monomers butyl acrylate, ethylene glycol dimethacrylate, and methyl silicone oil into a pre-emulsification bottle for pre-emulsification to obtain a core layer pre-emulsion; (3) pre-emulsifying the emulsifier solution (40% of the total emulsifier solution, i.e., the remaining emulsifier) ​​with the shell monomers styrene and methyl methacrylate (each taking 70% of the total amount) to obtain a shell pre-emulsified solution; (4) Take baking soda (0.2% of the weight of all monomers) and add 5 times the weight of deionized water into a reaction container, then take 5% of the core layer pre-emulsion and the initiator solvent (10%) and add them into the reaction container, carry out seed polymerization at 65°C, react for 30 minutes, and the emulsion becomes transparent to blue light; then, at 76°C, add the core layer pre-emulsion and the initiator solvent (the rest, add for 2 hours) dropwise to carry out core layer polymerization, react for 1 hour, and obtain an acrylate latex; (5) adding the shell monomers styrene and methyl methacrylate (30% of the total amount each) to the acrylic ester latex for primary grafting (dropping for 1 hour), reacting at 76°C for 1 hour, then adding the shell pre-emulsion to the reaction for secondary grafting, reacting at 76°C for 1 hour, and then naturally cooling to 40°C to obtain an ASA emulsion; (6) The ASA emulsion is then coagulated, dehydrated and dried to obtain ASA resin high-rubber powder. This is a conventional method, refer to Example 1.

[0061] The polymerization atmosphere was a nitrogen atmosphere.

[0062] Compared with the Tg (-43°C) of conventional commercially available ASA rubber powder, the Tg of the synthetic rubber powder of the present invention can reach -47°C, which solves the problem that the Tg of ASA rubber powder synthesized by the existing method is difficult to be lower than -45°C. In addition, the particle size of the rubber powder of the present invention is about 250nm, and the monomer conversion rate reaches more than 99.0%. Figure 1 The infrared spectrum of the ASA emulsion in Example 1 is shown in the FT-IR spectrum of the obtained emulsion at a wavelength of 2960 cm -1 The vibration absorption peak corresponds to the methyl vibration absorption peak, with a wavelength of 1731 cm -1 The vibration absorption peak corresponds to the vibration absorption peak of the C=O bond, with a wavelength of 1156 cm -1 The vibration absorption peak corresponds to the vibration absorption peak of the COC bond, indicating that the film structure has well maintained the ester and methyl structures of the polymerized monomers; the wavelength is 1060 cm -1 The vibration absorption peak corresponds to the vibration absorption peak of the Si-OC bond; the wavelength is 1454 cm -1 The vibration absorption peak corresponds to the CH bond deformation vibration absorption peak; the wavelength is 758 cm -1 The vibration absorption peak corresponds to the vibration absorption peak of the ester group, with a wavelength of 698 cm -1 The vibration absorption peak corresponds to the vibration peak of the monosubstituted benzene ring =CH bending outward. The vibration absorption peak of C=C does not appear at the wavelength of 1640 cm-1, which shows that BA, St, MMA, EGDMA and methyl silicone oil all participate in the copolymerization reaction, and ethylene glycol dimethacrylate and butyl acrylate are successfully cross-linked through CC bonds. The main chain structure of the polymer is still dominated by a saturated carbon chain structure, and ASA emulsion is synthesized.

[0063] Table 2 ASA rubber powder and SAN resin blending formula (Kg) and performance

[0064] The impact strength of pure SAN resin is 2.63 KJ / m 2 The low-temperature notched impact strength of 30% ordinary rubber powder (a ternary polymer composed of acrylonitrile, styrene and acrylic rubber) and SAN resin is 5 KJ / m 2 The low temperature notched impact strength of the rubber powder of the present invention can reach 6.5 KJ / m 2 Above, even more than 7 KJ / m 2 , while satisfying the effect of blackness L value and achieving a high gloss effect.

[0065] Comparison example The existing commercially available ASA rubber powder with good performance is mixed with SAN resin in a mass ratio of 3:7 and granulated by a twin-screw extruder. This is a conventional technology. The low-temperature notched impact strength is 6.07 / KJ / m 2 .

[0066] It can be seen that the present invention uses a significantly smaller amount of rubber powder than the prior art to achieve good performance, unexpectedly significantly improves the impact strength of the SAN material, and maintains excellent blackness, which is creative.

[0067] Heat resistance test of different rubber powders: placed in air environment at 150℃, the results are shown in Figure 2 It can be seen that under the condition of 150°C, the ordinary rubber powder and the BA-60 rubber powder (the rubber powder with good existing application) turned yellow after 24 hours, but the color of the rubber powder of Example 1 remained basically unchanged.

[0068] The present invention prepares rubber powder with good heat resistance and lower Tg by combining the amount of rubber phase, the selection and amount of functional monomers, and the emulsion polymerization system with the process flow. When used for SAN resin, the rubber powder can obtain very good low-temperature impact resistance under the condition of significantly low addition amount, which can reduce material costs and break technical limitations. In addition, methyl methacrylate is used to replace acrylonitrile polymerization, which reduces the harm of highly toxic substances and improves the heat resistance of the material. The low-temperature notched impact strength of the rubber powder after blending with SAN resin is ≥6.5kJ / m 2 .

Claims

1. A method for synthesizing low temperature resistant and high impact resistant ASA rubber powder, comprising the following steps: (1) adding part of the emulsifier solution, butyl acrylate, ethylene glycol dimethacrylate, and methyl silicone oil into a pre-emulsification bottle for pre-emulsification to obtain a core layer pre-emulsion; adding the remaining emulsifier solution, styrene, and methyl methacrylate into another pre-emulsification bottle for pre-emulsification to obtain a shell layer pre-emulsion; (2) Then, 1 to 10% of the core layer pre-emulsion and part of the initiator are added to a reaction vessel to carry out seed polymerization; then, the remaining core layer pre-emulsion is added dropwise to carry out core layer polymerization to obtain an acrylate latex; (3) 40-60% of the shell pre-emulsion and part of the initiator are added to the acrylic latex for a primary grafting reaction; then the remaining shell pre-emulsion and the remaining initiator are added for a secondary grafting reaction to obtain a low-temperature resistant and high-impact ASA rubber powder.

2. The method for synthesizing the low temperature resistant and high impact resistant ASA rubber powder according to claim 1, characterized in that: In step (1), the partial emulsifier solution is 40-60% of the total emulsifier solution; the pre-emulsification is carried out in water for 1-3 hours; in step (2), the seed polymerization is carried out in the presence of a pH buffer, and the partial initiator is 25-35% of the total initiator; the temperature of the seed polymerization is 60-70°C, and the time is 15-50 minutes; the temperature of the core layer polymerization is 75-80°C, and the time is 0.5-2 hours.

3. The method for synthesizing the low temperature resistant and high impact resistant ASA rubber powder according to claim 1, characterized in that: In step (3), the partial initiator is 25-35% of the total initiator; the temperature of the first grafting reaction is 75-80°C, and the time is 0.5-2 hours; the temperature of the second grafting reaction is 75-80°C, and the time is 0.5-2 hours.

4. The method for synthesizing the low temperature resistant and high impact resistant ASA rubber powder according to claim 1, characterized in that: The monomer composition is as follows: Butyl acrylate balance Styrene 20-40% Methyl methacrylate 5-15% Methyl silicone oil 2-8% Among them, the mass sum of the monomers is 100%.

5. The method for synthesizing the low temperature resistant and high impact resistant ASA rubber powder according to claim 1, characterized in that: Taking the total weight of monomers as 100%, the composition of additives is as follows: Emulsifier 0.5-1.5% Initiator 0.3-1% Crosslinking agent 0.1-0.3%.

6. ASA rubber powder synthesized by the synthesis method of low-temperature-resistant and high-impact ASA rubber powder according to claim 1.

7. A modified SAN resin, comprising the ASA rubber powder according to claim 6 and SAN resin.

8. The method for preparing the modified SAN resin according to claim 7, comprising the following steps: melt-mixing the raw materials comprising the ASA rubber powder according to claim 6 and the SAN resin to obtain the modified SAN resin.

9. Use of the ASA rubber powder according to claim 6 in the preparation of modified SAN materials, automotive SAN materials or automotive materials; or use of the ASA rubber powder according to claim 6 in improving the low-temperature impact resistance of SAN materials.

10. An automobile part, wherein the raw materials for preparing the automobile part include the ASA rubber powder as claimed in claim 6 or the modified SAN resin as claimed in claim 7.

Citation Information

Cited By

  • Low-temperature-resistant and moisture-resistant wood-like flow-line color ASA resin, and preparation and application thereof

    CN122668485A